Estratégia de internacionalização de uma cooperativa do agronegócio: o caso Frimesa - Maróstica, Magali (2008)
This study discusses the applicability of the internationalization schools of thought to the internationalization process of a cooperative enterprise, a type of organization that has not yet been studied much. The work is exploratory and is based on a case study in which the internationalization strategies of Frimesa (an agricultural cooperative enterprise in the state of Parana, Brazil) were analyzed in order to check if the internationalization approaches described in the literature were applicable to a cooperative enterprise. Different theoretical trends were studied that deal with the internationalization issue. The study was concerned with the strategic focus that underlies the use of internationalization models, checking their suitability for cooperative ventures. Semi-structured interviews were carried out with Frimesa’s managers and directors in order to understand the organization’s internationalization process. To improve the validity and reliability of the qualitative process, different data sources were used. In addition to several interviews with different people, document research was also carried out internally and externally to the organization. When Frimesa was analyzed and compared to the different schools of thought that exist in the literature, Frimesa’s strategy was closer to the traditional behavioral school’s approach than to the modern behavioral school’s, which discusses the importance of networks in the internationalization strategy. This is an important result considering that Frimesa is a cooperative enterprise, which has, as its essential principle the development of inter-cooperation. In that sense, the formation of networks should take place in a natural way within cooperative enterprises, leveraging their internationalization processes. However, that was not noticed at Frimesa. On the other hand, the economical approaches were able to explain part of Frimesa’s internationalization process by means of the eclectic paradigm and the internalization theory. Internationalization, by means of the verticalization of its activities, is considered strategic for Frimesa, representing its source of international competitive advantage. The same way, the organization’s localization and the formation of a cluster around it is another source of advantage, helping Frimesa to achieve a lower final cost for its product, making it compatible anywhere in the world.